The Digital Revolution in Sports: Analyzing the Impact of Information Technology on Athlete Training and Management - Suyudi, Imam (Manunggal Halim Jaya, 2023)
The digital era has brought about significant transformations across various aspects of life, including the world of sports. This study aims to delve deeply into how information technology (IT)—encompassing big data, IoT, wearable technologies, AR, and VR—has shifted the paradigms of athlete training and management. Employing both quantitative and qualitative approaches, this research explores the impact of IT on training efficiency, injury risk reduction, and athlete performance enhancement. By collecting data from coaches, sports managers, and athletes across different sports disciplines, this study tests the proposition that IT integration in sports not only elevates athlete performance but also redefines training practices and sports management strategies. This research is expected to provide new insights that can be utilized by coaches, sports managers, and policymakers to effectively harness information technology in enhancing athlete performance and optimizing sports management. Furthermore, these findings are anticipated to spur further discussion on the future of technology in sports and how it can continue to be used to push the boundaries of human performance.